Making A Third Force: Antonio Genovesi and the Teaching of Science in Enlightenment Naples. - Quinlan, Sean M. (Journal for Early Modern Cultural Studies)
This article examines how the philosopher and economist Antonio Genovesi (1713–1768), one of the outstanding figures of the Italian Enlightenment, published a trilogy of popular books on science and philosophy, all geared towards educating the youth of the Kingdom of Naples and Sicily. Genovesi hoped these books would turn the young children of the patrician and feudal elite into an enlightened and ethical ruling class, one that would lead and aggressively reform Neapolitan society. Science taught young people virtuous norms and a common way of understanding the individual, society, and nature; it allowed them to comprehend the surrounding world, diagnose its fundamental problems, and act upon their consciences. Though Genovesi's project found disciples amongst the Italian intelligentsia, they often saw this project as a superhuman task. Rather than instigating a wave of specific trade and technology initiatives, Genovesi inspired new forms of social thought and historical and autobiographical reflection, geared toward understanding the social and political singularity of the Italian south.